2005
DOI: 10.1152/ajpcell.00394.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide- and gram-positive bacteria-induced cellular inflammatory responses: role of heterotrimeric Gαi proteins

Abstract: Heterotrimeric G(i) proteins may play a role in lipopolysaccharide (LPS)-activated signaling through Toll-like receptor 4 (TLR4), leading to inflammatory mediator production. Although LPS is a TLR4 ligand, the gram-positive bacterium Staphylococcus aureus (SA) is a TLR2 ligand, and group B streptococci (GBS) are neither TLR2 nor TLR4 ligands but are MyD88 dependent. We hypothesized that genetic deletion of G(i) proteins would alter mediator production induced by LPS and gram-positive bacterial stimulation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
41
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 67 publications
7
41
1
Order By: Relevance
“…In the present study, the total numbers of cells and specifically, neutrophils recruited into the micro-environment of the larvae were significantly lower in Gαi2 −/− mice as compared with wild-type mice. This confirms previous observations that disruption of signaling through Gαi proteins inhibits cell migration and recruitment to infection sites [35][36][37] and contradicts studies that demonstrated that Gαi2 −/− mice have equal or enhanced MPO levels, used as a measurement of neutrophil recruitment in the gut, liver, or lung following exposure to LPS [38]. It is clear from the present study that Gαi2 is required for neutrophil recruitment to the s.c. microenvironment of the nematode parasite.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the total numbers of cells and specifically, neutrophils recruited into the micro-environment of the larvae were significantly lower in Gαi2 −/− mice as compared with wild-type mice. This confirms previous observations that disruption of signaling through Gαi proteins inhibits cell migration and recruitment to infection sites [35][36][37] and contradicts studies that demonstrated that Gαi2 −/− mice have equal or enhanced MPO levels, used as a measurement of neutrophil recruitment in the gut, liver, or lung following exposure to LPS [38]. It is clear from the present study that Gαi2 is required for neutrophil recruitment to the s.c. microenvironment of the nematode parasite.…”
Section: Discussionsupporting
confidence: 92%
“…This is in contrast to neutrophils recovered from TLR4-deficient mice, which were able to migrate to the parasite but were unable to kill the worms [24]. Although TLR4 and Gαi are linked in their activation and function [23,38], it can be concluded from the present study that Gαi2 protein is not required for TLR4-dependent neutrophil killing of the larvae. Neutrophils from TLR4-deficient mice cannot kill larvae [24], although they migrate to the site, whereas neutrophils from Gαi2-deficient mice can kill the larvae as efficiently as wild-type cells only if they are transported experimentally to the site of infection.…”
Section: Discussioncontrasting
confidence: 88%
“…Heterotrimeric guanine nucleotidebinding regulatory (Gi) proteins modulate LPS signaling pathways and downstream pro-inflammatory gene expression (4)(5)(6)(7). In addition to toll-like receptor (TLR) 4, LPS also binds to a cluster of receptors in lipid rafts, some of which are Gi protein coupled (8).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to toll-like receptor (TLR) 4, LPS also binds to a cluster of receptors in lipid rafts, some of which are Gi protein coupled (8). Our previous studies demonstrated that LPS-induced inflammatory cytokines and chemokines were augmented in vitro and in vivo in Gi proteindeficient mice compared with WT mice, suggesting an anti-inflammatory role of Gi proteins (5,6). Gi protein-coupled ERK 1/2 signaling pathway mediates LPSinduced signaling (4).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic deletion of the G␣ i isoforms (G␣ i1 , G␣ i2 , and G␣ i3 ) suggests that G ␣i proteins differentially regulate TLR-stimulated cytokine production in a cell-type specific manner (16). However, the role of G␣ i/o proteins in TLR4 signaling in endothelial cells remains less well understood and the role of G␣ i/o in TLR signaling cascades other than TLR4 has not been shown.…”
mentioning
confidence: 99%